New Software Testing Method Based on Evolutionary Algorithm - Khosravi, Samiyeh; ., . (International Journal of Engineering and Technology, 2018)
Software Testing is an important part of software development which is performed to support and enhance reliability and quality of software. It consists of estimating testing effort, selecting suitable test team, designing test cases, executing the software with those test cases and examining the results produced by these methods. This paper proposes Fuzzy Based approach for finding out the complexity weight based on requirement. Based on the weight, this paper computes the software complexity point. Fuzzy logic uses membership functions to include linguistic variables and quantifiers. Fuzzy Logic could be used in project estimation purposes efficiently by gathering size data on previously developed programs. The advantage of this model is that it is able to estimate the software complexity which in turn predicts the software requirement stability during the software development cycle.Â Â Â